KNUCKLE-WALKING: PRELUDE TO HOMININ BIPEDALTY OR ACQUIRED MECHANISM TO PROTECT FINGERTIPS? - Kumar, Arunachalam (Journal of Health and Allied Sciences NU, 2012)
The exact period, cause and evolution of erect posture and bipedal gait in early hominids has subject of much debate among primatologists and anthropologists. This brief presentation proposes at least that one among the theories, knuckle-walking as a precursor to bipdality is probably debatable. In higher apes, which spend more time on foraging at terrestrial level and less as arboreal primates, knuckle walking may have evolved more as a nail and fingertip protective adaptation in apes.
Keywords: knuckle-walking; bipedal gait; hominin; Australopithecus; apes